Movement, Behavior, and Habitat Use of a Marine Apex Predator, the Scalloped Hammerhead - Wells, R. J. David; TinHan, Thomas C.; Dance, Michael A.; Drymon, J. Marcus; Falterman, Brett; Ajemian, Matthew J.; Stunz, Gregory W.; Mohan, John A.; Hoffmayer, Eric R.; Driggers, William B.; McKinney, Jennifer A. (Frontiers in Marine Science, 2018)
Conservation and management efforts of marine apex predators are more reliable when information on movement and habitat use patterns are known. The scalloped hammerhead (Sphyrna lewini) was the first shark species to be protected under the U.S. Endangered Species Act and has life history characteristics that make this species particularly at risk for local depletion. Consequently, the goal of this study was to better understand the movement dynamics of this species in the Gulf of Mexico (GOM) where discards through the longline fishery can be substantial. A total of 33 scalloped hammerheads were tagged with fin mounted satellite tags and tracked for an average of 146 days (ranging from 5 to 479 days) to examine horizontal movements and quantify space use. Scalloped hammerheads showed a wide range of movements throughout the GOM continental shelf with limited long-distance dispersal and females displayed a shelf-edge association relative to more mid-shelf use by males. A generalized additive model was developed to identify habitat suitability for scalloped hammerheads in the GOM, while state-space modeling was used to examine movement behaviors. Model results highlighted the use of continental shelf waters with high occurrence at close proximities to both artificial and hard-bottom habitat combined with low chlorophyll a concentrations (~0–4 mg m-3) and moderate salinities (33–35.5). Habitat suitability for scalloped hammerheads was predicted to be high on the mid to outer continental shelf inside the 200 m isobaths and state-space models support area-restricted behavior was most common relative to transient behavior. Findings from this study provide important information on movement of this species in the GOM and highlight their restricted use of continental shelf habitat and resident behavior that will need to be incorporated in future stock assessments and extinction risk analyses.